Harnessing natural feed additives for sustainable production and economics: the role of Thymus vulgaris L. oil as an antimicrobial agent and a growth promoter in improving production and health of broiler chickens - Saied, Ahmed M.; Attia, Adel I.; Reda, Fayiz M.; El-Kholy, Mohamed S.; Al-Badwi, Mohammed A.; Azzam, Mahmoud; Di Cerbo, Alessandro; Alagawany, Mahmoud; El-Tarabily, Khaled A.; EL Nagar, Ayman G. (Frontiers in Immunology, 2025)
IntroductionThis study examined the effects of adding thyme oil (TO) to broiler diets on growth performance, intestinal health, immune organ indices, blood biochemical parameters, and economic feasibility.MethodsIn a completely randomized block design, five groups of 1-day-old broiler chicks (n=300) with five replicates, each consisting of 12 chicks, were used. A basal diet (BD) was supplied to the control group, whereas the other groups received BD supplemented with 75, 150, 225, and 300 mg/kg of TO.Results and discussionThe findings indicated that TO improved final body weight (BW), total body weight gain (BWG) and the feed conversion ratio (FCR), without affecting feed intake (FI). Groups fed 150, 225, and 300 mg/kg of TO showed higher levels of digestive enzymes (P<0.05) than the control. Supplementation with TO elevated immune organ indices, with statistical significance (P<0.05) noted in birds receiving 150, 225, and 300 mg TO/kg for the spleen, thymus, and bursa of Fabricius indices, compared with the control group. Moreover, total protein, globulin, immunoglobulin (IgM and IgG), and complement component 3 were significantly (P<0.05) higher by TO at 150, 225, and 300 mg/kg than at 0 and 75 mg/kg. Blood Ca and Mg were significantly (P<0.05) increased by the application of 150, 225, and 300 mg TO/kg, whereas the Fe level rose (P<0.05) by 75 and 150 mg/kg compared with the control. TO at 150, 225, and 300 mg/kg increased hemoglobin (Hb), counts of white blood cells (WBCs), and red blood cells (RBCs) compared with the control. The application of TO decreased (P<0.05) aspartate aminotransferase (AST) levels in a dose-dependent manner. Creatinine and urea levels were significantly decreased by TO at 225 and 300 mg/kg compared with the control. Lipid peroxidation was significantly (P<0.05) decreased by TO supplementation (150, 225, and 300 mg/kg), whereas superoxide dismutase (SOD), total antioxidant capacity (TAC), catalase (CAT), and reduced glutathione (GSH) were significantly increased by the application of 150, 225, and 300 mg TO/kg compared with the control. Lower levels of total cholesterol, triglycerides, low-density lipoprotein (LDL), and very low-density lipoprotein (VLDL) were observed at 75, 150, 225, and 300 mg TO/kg compared with 0 mg/kg. In comparison, higher high-density lipoprotein (HDL) levels were observed for 225 and 300 mg of TO/kg compared with the control. The net revenue and economic efficiency of TO-supplemented treated broilers were improved during the experiment (1–6 weeks of age). The best values of economic indices were observed in the group receiving 150 mg/kg of TO. Collectively, supplementation with dietary TO enhanced growth performance, intestinal health, immune system development and function, liver and kidney function, and antioxidant capacity, regulated the lipid profile, and improved economic feasibility.